2011
DOI: 10.1682/jrrd.2010.05.0081
|View full text |Cite
|
Sign up to set email alerts
|

Medical utilization and cost outcomes for poststroke veterans who receive assistive technology devices from the Veterans Health Administration

Abstract: Abstract-The study objectives were to (1) advance understanding of the relationship between provision of assistive technology devices (ATDs) and healthcare consumption and outcomes in a system that does not limit provision of ATDs to in-home use and (2) determine how the provision of ATDs relates to inpatient/outpatient utilization and costs of services for veterans 12 months poststroke when controlling for casemix. This was a retrospective study using Department of Veterans Affairs administrative/workload dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Of the included studies, 10 were conducted in the United States (USA) (Garber et al., 2002; Gitlin, 1998; Hubbard et al., 2006; Hubbard Winkler et al., 2010a, 2010b, 2011; Mann et al., 1995; Mountain et al., 2010a, 2010b, 2014; Prangrat et al., 2000; Skolarus et al., 2014), five in the UK (Barrett et al., 2001; Lennon, 1991; Punt et al., 2008, 2011; Turton et al., 2009; Tyson and Rogerson, 2009), three in Sweden (Gosman-Hedstrom and Blomstrand, 2003; Gosman-Hedstrom et al., 2002a, 2002b; Pettersson et al., 2006, 2007b, 2007a), three in Canada (Barker et al., 2004, 2006; Jutai et al., 2007; Reid et al., 2001; Rudman et al., 2006), and one each in Hong Kong (Chiu and Man, 2004), Switzerland (Allet et al., 2009), Germany (Hesse et al., 1996), Denmark (Sorensen et al., 2003), Israel (Laufer, 2003) and Korea (Kim and Kim, 2015). Four studies were randomised control led trials (RCTs) (Barrett et al., 2001; Chiu and Man, 2004; Mountain et al., 2014; Tyson and Rogerson, 2009), while others primarily used either descriptive designs such as cross-sectional or cohort frameworks, at times in combination with economic evaluations, or they consisted of qualitative research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, 10 were conducted in the United States (USA) (Garber et al., 2002; Gitlin, 1998; Hubbard et al., 2006; Hubbard Winkler et al., 2010a, 2010b, 2011; Mann et al., 1995; Mountain et al., 2010a, 2010b, 2014; Prangrat et al., 2000; Skolarus et al., 2014), five in the UK (Barrett et al., 2001; Lennon, 1991; Punt et al., 2008, 2011; Turton et al., 2009; Tyson and Rogerson, 2009), three in Sweden (Gosman-Hedstrom and Blomstrand, 2003; Gosman-Hedstrom et al., 2002a, 2002b; Pettersson et al., 2006, 2007b, 2007a), three in Canada (Barker et al., 2004, 2006; Jutai et al., 2007; Reid et al., 2001; Rudman et al., 2006), and one each in Hong Kong (Chiu and Man, 2004), Switzerland (Allet et al., 2009), Germany (Hesse et al., 1996), Denmark (Sorensen et al., 2003), Israel (Laufer, 2003) and Korea (Kim and Kim, 2015). Four studies were randomised control led trials (RCTs) (Barrett et al., 2001; Chiu and Man, 2004; Mountain et al., 2014; Tyson and Rogerson, 2009), while others primarily used either descriptive designs such as cross-sectional or cohort frameworks, at times in combination with economic evaluations, or they consisted of qualitative research.…”
Section: Resultsmentioning
confidence: 99%
“…(2006) strongly indicated that there was inequity with wheelchair provision attributable to ethnic background, where Hispanics (OR = 1.864), African Americans (OR = 1.360) and American Indians/Asians (OR = 1.585) were more likely than Caucasians to receive standard wheelchairs, rather than powered wheelchairs or scooters. With the exception of research conducted by Hubbard Winkler et al. (2011) in recent years, the lack of high-quality evidence about the cost of equipment after stroke makes policy decisions in this area challenging, and means it is difficult to quantify the degree of unmet need (Skolarus et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results by Teasell et al [12] and Preston et al [13] show contrary increase in AT provision with time after CVA. But provision of expensive AT devices, such as scooters, power wheelchairs, and selected walking aids can be associated with costs [6]. Previous results by Mikołajewska concerning wheelchair use in patients after ischemic stroke show similar tendency to decrease wheelchair use with time after CVA: -71% three weeks to three months after CVA, -42% three months to six months after CVA, -20% six months to three years after CVA [14].…”
Section: Resultsmentioning
confidence: 93%
“…Assistive technology (AT) is regarded as one of the most important factors influencing functional recovery and independence in patients after stroke. There is still a need for research on predictors and early identification of AT requirements in order to shape and maximize its positive influence to the recovery process [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%